Improving success of rare plant seed reintroductions: a case study of Dalea carthagenensis var. floridana, a rare legume with dormant seeds. Issue 4 (16th October 2017) - Maschinski, Joyce; Possley, Jennifer; Walters, Christina; Hill, Lisa; Krueger, Lisa; Hazelton, Dallas
Abstract : Recent reviews of rare plant reintroduction success indicate that far fewer studies have been conducted with seeds than whole plants, and of these, less than 10% have established or had long‐term population persistence reported. Because seed reintroductions are relatively less expensive than plant reintroductions, determining ways to increase efficacy of using seeds to establish rare populations has conservation benefits. In laboratory trials, we examined seed germination of an endangered legume, Dalea carthagenensis var. floridana, endemic in South Florida, U.S.A. Laboratory treatments confirmed that seeds are hard seeded, remaining viable for 1, 452 days even when moist; nicking, heat, and freezing triggered higher and more rapid germination than controls. Field trials begun in 2009, using pretreated (frozen) and untreated seeds within two habitats (natural and novel) revealed that freezing pretreatment increased germination in both habitats. However, plants matured, reproduced, and established seedlings only in natural habitat, not in novel habitat. By 2012, seed treatment plots in natural pine rockland had significantly greater numbers of reproductive plants and seedlings than controls. In a restoration context, using seed pretreatments to stimulate germination can improve establishment success in suitable habitats. When paired with essential vegetation management and a controlled burn, seed augmentation helped rescue the population from the brink of extinction.